Emergency Separation of Extreme VLBW Omphalopagus Twins: Case Report - Waleed Burhamah; Amar Alnaqi; Yaqoub Jafar; Esmaeel Taqi (European Journal of Pediatric Surgery Reports, 2022)
The classification of conjoint twins is based according to the site of attachment. The challenges in management of such anomalies span the entire continuum of care from delivery to resuscitation to separation and finally discharge. Scheduled separation is ideal, occasionally the caring team is faced with no option but to perform an emergent separation. Omphalopagus is a type of conjoined twinning characterized by union of the peritoneal cavities through an infraumbilical abdominal wall defect. In this report we describe our experience with a successful emergency separation of extremely preterm omphalopagus twins. This is the first case of conjoint twins in Kuwait, we highlight the challenges faced, stressing the importance of adhering to antenatal care as well as management by a multidisciplinary team.